Irracional teńlemelerdi sheshiwdiń bazı bir usılları - Asqarov, M (SCIENCE and SOCIETY, 2020)
The author of the article describes some methods of solving irrational equations.
Keywords: equation; irrational equation; trigonometric substitution method